"The metabolic syndrome... is dead": These reports are an exaggeration - Tenenbaum, Alexander (BioMed Central, 2011)
The debates continue over the validity of the metabolic syndrome concept. The continuous increment of the obesity pandemic is almost worldwide paralleled by rising rates of metabolic syndrome prevalence. Then, it seems obvious that these debates drove the need for further investigations as well as a deeper cooperation between relevant national and international organizations regarding the issue. Instead, part of the scientific community elected to totally "dismiss" the concept of the metabolic syndrome. Meanwhile, the best available evidence from three consecutive large meta-analyses has systematically shown that people with metabolic syndrome are at increased risk of cardiovascular events. The most recent and largest of them included near one million patients (total n = 951,083). The investigators concluded that the metabolic syndrome is associated with a 2-fold increase in cardiovascular outcomes and a 1.5-fold increase in all-cause mortality rates. One of the ways to hit the metabolic syndrome is an utterly simplistic view on this concept as a predictive tool only. Of course, the presence of the metabolic syndrome possesses a definite predictive value, but first of all it is a widely accepted concept regarding a biological condition based on the complex and interrelated pathophysiological mechanisms starting from excess central adiposity and insulin resistance. Therefore, it is completely unfair to compare it with statistically constructed predictive tools, including stronger prognostic variables even unrelated to each other from the biological point of view. For example, in the criteria for metabolic syndrome (in contrast to Framingham score) age and cholesterol - presumably low density lipoprotein - cholesterol (LDL-C) - levels are not included, as well as a variety of strong predictors used in other risk-stratification scores: previous myocardial infarction, heart failure, smoking, family history, etc. However, the metabolic syndrome identifies additional important residual vascular risk mainly associated with insulin resistance and atherogenic dyslipidemia (low high density lipoprotein-cholesterol (HDL-C), high triglycerides, small, dense LDL-C). Therefore, the metabolic syndrome could be a useful additional contributor in estimation of global cardiovascular risk beyond age, high LDL-C or other standard risk factors. The components of the metabolic syndrome have partially overlapping mechanisms of pathogenic actions mediated through common metabolic pathways. Therefore their total combined effect could be less than the summed of the individual effects. The concept that the metabolic syndrome is a consequence of obesity and insulin resistance, provides a useful "life-style changes" approach for prevention and treatment: caloric restriction, weight-loss and increased physical activity. The next step could theoretically be pharmacological interventions such as metformin, acarbose, fibrates, weight-loss drugs (currently only orlistat is practically available) and perhaps glucagon-like peptide-1 agonists. A third step should probably be kept for bariatric surgery.